Fatores associados á mortalidade, morbidade e desempenho de bezerras em aleitamento - Matheus Balduino Moreira (2019)
Heifer rearing represents a large cost for dairy enterprises, but data on risk factors for failure of transfer of passive immunity in tropical countries is scarce. Our objective was to describe risk factors for failure of transfer of passive immunity (FTPI) and to investigate how FPTI is associated with the risk of morbidity, mortality, and growth of pre-weaned dairy calves from two genetic compositions in tropical conditions. We performed a retrospective cohort study and used pre- and post-birth calf-level data from 6,011 crossbred pre-weaned calves from a single herd, born between 2012-2018. We obtained information on calf pedigree, the season of birth, the occurrence of retained placenta (RP), total serum protein (TSP), morbidity (neonatal calf diarrhea - NCD, bovine respiratory disease - BRD, and tick-borne disease - TBD), mortality, and weight gain. The genetic composition was predominantly dairy Gyr (PG, 0-50% Holstein breed), and predominantly Holstein (PH, > 50% Holstein breed). Multivariate mixed logistic regression was performed (SAS 9.4). The optimal TSP cut-off points for predicting morbidity and mortality were 7.6 g/L and 6.9 g/L, respectively. The median value of TSP was 7.2 g/L. At cut-off points of 5.2 g/L, 7.6 g/L, and 6.9 g/L the prevalence of FTPI was 2%, 55%, and 31%. PH calves had 1.35 greater odds of having FTPI, and 1.48 greater odds of disease. Calves born from multiparous cows and from calving followed by RP had greater odds of FTPI. Overall, the prevalence of disease was 53%, and 41% of the calves had NCD, 18% had BRD, 10% had TBD. Season, parity order of the dam, sire predicted transmitted ability for mil (PTA milk), and weight at birth were also associated with odds of disease. FTPI was not a good predictor of disease. The overall mortality rate was 6%. Calves PH had 2.99 greater odds of mortality than PG. The mortality risk varied according to an interaction between FTPI and the season of birth, but calves from sires with a positive PTA for milk had greater odds of dying. The average daily gain was 0.636, and calves with FTPI (cut-off point of 5.2 g/L) gained less weight than calves without FTPI. An adequate transfer of passive immunity may not be enough to prevent morbidity and mortality if calves are raised in challenging conditions. Keywords: failure of transfer of passive immunity, neonatal calf diarrhea, bovine respiratory disease, cattle tick fever.